PERANCANGAN BUKU CERITA BERGAMBAR ANGGUN NAN TONGGA (CERITA RAKYAT PARIAMAN) - RIZALLUN FIQRI, San Ahdi, S.Sn., M.Ds., Elya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Folklore is a story that comes from a society and has evolved into a cultural characteristic. The author raised the story of the people of Pariaman namely Anggun Nan Tongga. The purpose of this design is in the form of comic book Anggun Nan Tongga and other supporting media to provide information directly and delivery of more detailed, communicative and effective. The method used in data collection is by conducting interviews, literature studies, observation, and documentation. While the method used to analyze the data is 5W + 1H analysis. The main media used in this design is the book while the supporting media used are t-shirts, x-banners, bookmarks, fans, stickers, wall clocks.Keywords : Folklore, Comic, Anggun Nan Tongga